2021
DOI: 10.3389/fncel.2021.738533
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Exogenous Irisin in Kainic Acid-Induced Status Epilepticus

Abstract: Graphical AbstractOur study confirmed significant anti-oxidative stress and neuroprotective effects of exogenous irisin in KA-induced SE. Moreover, the BDNF/UCP2 pathway may contribute to the mechanism underlying the neuroprotective effects of irisin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Physical exercise increases BDNF levels through PGC-1α activation and modulation of FNDC-5 expression (46). With the studies conducted in recent years, it has been confirmed that irisin exerts its neuroprotective effects by increasing the expression of BDNF (43,46). Considering the neuroprotective roles of irisin in accordance with previous studies, it is considered that both exogenous and endogenous irisin may provide protection against epilepsy-induced neuronal damage (43).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Physical exercise increases BDNF levels through PGC-1α activation and modulation of FNDC-5 expression (46). With the studies conducted in recent years, it has been confirmed that irisin exerts its neuroprotective effects by increasing the expression of BDNF (43,46). Considering the neuroprotective roles of irisin in accordance with previous studies, it is considered that both exogenous and endogenous irisin may provide protection against epilepsy-induced neuronal damage (43).…”
Section: Discussionmentioning
confidence: 66%
“…It has been demonstrated that irisin, an exercise-related hormone, can improve the mitochondrial functions and protect against many diseases by reducing the production of reactive oxygen species (ROS) (41). With various studies conducted in parallel with this, it has been confirmed that exogenous irisin treatment improved the mitochondrial dysfunction and significantly reduces the ROS levels (42,43).…”
Section: Discussionmentioning
confidence: 96%
“…After administering pentobarbital sodium (50 mg/kg, intraperitoneally, CAS, 57-33-0, Xiya Reagent, Chengdu, China), the brain was quickly removed, and the cortex and hippocampus were separated on ice, following which 0.01M PBS (10 μL/mg) was added to the samples, which were then cut using scissors on ice. Sequentially, the cut issue was filtered through a stainless steel mesh (200 mesh/inch) for the single-cell suspensions ( Cheng et al, 2021 ). In accordance with the instructions of the ROS Assay Kit (Beyotime, S0033, Shanghai, China), 500 μL DCFH-DA diluted with serum-free culture medium (1:1000, 10 μM/L) were added to the single cell suspensions (250 μL) for 40 min incubation at 37°C without daylight.…”
Section: Methodsmentioning
confidence: 99%
“…It seems feasible that irisin is implemented in the realization of the mechanical link between exercises and changes in the neuronal cells leading, in analogy to peripheral effects, to adaptive adjustment of lipid metabolism, cellular excitation, and antioxidant systems in neurons and glia ( Stranahan et al, 2010 ). Effects of exogenous irisin ( Cheng et al, 2021 ) or irisin gene knockdown ( Islam et al, 2021 ) on animals’ behavior indicate that it also provides a functionally relevant signaling in the brain.…”
Section: Irisin Is Linking Pes To Neuroplasticity and Autophagy In Th...mentioning
confidence: 99%
“…The myokine irisin initially garnered attention for its paracrine signaling leading to white to brown fat cell transformation and, upon its chronic action, to adaptation of muscle and bone tissue to increased physical load ( Li H. et al, 2019 ; Waseem et al, 2022 ). However, effects of exogenous irisin ( Cheng et al, 2021 ) or irisin gene knockdown ( Islam et al, 2021 ) on animals’ behavior indicate that endogenous irisin stands behind activation of the muscle-brain axis and act as signaling molecule in the brain.…”
Section: Introductionmentioning
confidence: 99%